Tensiones entre democracia y populismo: una aproximación desde la opinión pública - Badillo Sarmiento, Reynell (2019)
Populism has been a phenomenon widely studied in Latin America. However, his analysis has been focused on the implications that it has for democracy. In contrast, little inquiry has been conducted about the unknown effects on the democratic conceptions of the population. This research investigates how citizen attitudes are affected in relation to the political system when there is a constant undermining of democratic institutions by populist politicians? In that sense, the cases of Venezuela, Ecuador and Bolivia are analyzed based on data from the Barometer of the Americas that allow examining the degree of democratic legitimacy in these countries during the governments of Hugo Chavez, Rafael Correa and Evo Morales, who are considered "politicians with populist features". It is concluded that, although the arrival of populist politicians in Latin America during the first decade of the millennium was partly due to a crisis of democratic legitimacy of citizens, it is necessary to take into account that populist political projects failed to develop democratic values in the population. On the contrary, the tendency is usually that support for the political system increases considerably (usually confused with executive support) while political tolerance decreases or remains unstable. While a decrease in the institutional quality of democracy was taking place, the citizenship moved from a democracy at risk (low system support and low political tolerance) to authoritarian stability (high system support and low political tolerance).